Coming of age: coaches transforming the pixie-style model of coaching in women`s artistic gymnastics - Kerr, R.; Barker-Ruchti, N.; Schubring, A. (Sports Coaching Review, 2017)
Coaches and coach educators have recognised the difficulty of creating changes to traditional coaching practice. In this article, we draw on interviews with five successful coaches who, we argue, engaged in actively changing their gymnastics coaching practice through promoting alternative "games of truth" which challenged the authoritarian women`s gymnastics coaching model. This alternative truth game included a focus on energy levels (over thinness) and a belief that older gymnasts can learn new skills and be successful, which led to adaptations of their coaching. We demonstrate how coaches` experiences of coaching older gymnasts and their observations of successful gymnasts` older ages and powerful physiques produced critical reflections of their former views, which led to the recognition of alternative truths. This article illustrates the possibility of coaches changing their coaching practices, although we found that coaches were motivated by success rather than athlete empowerment